Developing and maintaining practical archives : a how-to-do-it manual - Hunter, Gregory S. (Chicago : ALA Neal-Schuman, 2020)
"Providing in-depth coverage of both theory and practice, this manual is essential for archivists at all levels of experience and of all backgrounds"--
Introduction to archives and manuscripts -- Surveys : identifying records on all media -- Starting an institutional or community archives -- Selection and appraisal -- Acquisitions and accessioning -- Arrangement -- Description -- Preservation -- Security and disaster planning -- Access, reference, outreach, and advocacy -- Leadership and management -- The archival profession.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on May 29, 2020).
eBooks on EBSCOhost
Keywords: Archives -- Handbooks, manuals, etc; Archives -- Guides, manuels, etc; Archives; Handbooks and manuals